Biocatalytic approach for the utilization of hemicellulose for ethanol production from agricultural residue using thermostable xylanase and thermotolerant yeast - Menon, Vishnu; Prakash, Gyan; Prabhune, Asmita; Rao, Mala (Bioresource Technology, 2010)
A hydrolysis of 62% and 50% for OSX (Oat spelt xylan) and WBH (Wheat bran hemicellulose) were obtained in 36 h and 48 h using Accellerase(TM) 1000 at 50 degrees C wherein thermostable xylanase from alkalothermophilic Thermomonospora sp. yielded 67% (OSX) in 3 h and 58% (WBH) in 24 h at 60 degrees C, favouring a reduction in process time and enzyme dosage. The rate of hydrolysis with thermostable xylanase was increased by 20% with the addition of nonionic surfactant tween 80 or biosurfactant sophorolipid. The simultaneous saccharification and fermentation (SSF) of OSX and WBH using thermostable xylanase and D. hansenii in batch cultures produced 9.1 g/L and 9.5 g/L of ethanol, respectively and had a shorter overall process time than the separate hydrolysis and fermentation (SHF). The immobilized yeast cells in Ca-alginate matrix produced ethanol with a yield of 0.46 g/g from hemicellulosic hydrolysates and were reused six times with 100% fermentation efficiency. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Biosurfactant; Ethanol; Hemicellulose; Thermostable xylanase; Thermotolerant yeast

Enzymatic hydrolysis and ethanol production using xyloglucanase and debaromyces hansenii from tamarind kernel powder: galactoxyloglucan predominant hemicellulose - Menon, Vishnu; Prakash, Gyan; Rao, Mala (Journal of Biotechnology, 2010)
The hydrolysis and ethanol production from tamarind kernel powder (TKP), a rich source of galactoxyloglucan (GXG) was investigated for the first time using xyloglucanase and thermotolerant Debaromyces hansenii. The acid hydrolysis of TKP with 2N H(2)SO(4) at 120 degrees C for 30 min yielded an overall saccharification of 94% based on the total available carbohydrate content and further fermentation at 40 degrees C with thermotolerant D hansenii produced an ethanol yield of 0.35 g/g. A maximum hydrolysis of 55 and 78% for GXG was obtained in 48 h at 50 degrees C using Thermomonospora xyloglucanase (TXy) and accellerase (TM) 1000, respectively. The synergistic effect of beta-galactosidase and xyloglucanase was demonstrated by the exogenous addition of beta-galactosidase to TXy which improved the overall hydrolysis of GXG by 30%. The rate of hydrolysis of GXG with TXy and accellerase was increased by 15-20% in the presence of chemical surfactants (tween 80 and toluene) or protein additive (BSA). The fermentation of enzymatic hydrolysates of GXG by TXy and accellerase with free cells at 40 degrees C produced an ethanol yield of 0.39 and 0.41 g/g whereas with immobilized cells produced 0.45 and 0.43 g/g, respectively, with a theoretical conversion efficiencies of 78-88%. The immobilized yeast cells were reused six times at 40 degrees C with 100% fermentation efficiency. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Ethanol; Galactoxyloglucan; Hydrolysis; Tamarind kernel powder; Thermotolerant yeast; Xyloglucanase

Microbial production of xylitol from D-xylose and sugarcane bagasse hemicellulose using newly isolated thermotolerant yeast Debaryomyces hansenii - Prakash, Gyan; Varma, Anjanikumar; Prabhune, Asmita; Shouche, Yogesh; Rao, Mala (Bioresource Technology, 2011)
A thermotolerant yeast capable of fermenting xylose to xylitol at 40 C was isolated and identified as a strain of Debaryomyces hansenii by ITS sequencing. This paper reports the production of xylitol from D-xylose and sugarcane bagasse hemicellulose by free and Ca-alginate immobilized cells of D. hansenii. The efficiency of free and immobilized cells were compared for xylitol production from D-xylose and hemicellulose in batch culture at 40 degrees C. The maximum xylitol produced by free cells was 68.6 g/L from 100 g/L of xylose, with a yield of 0.76 g/g and volumetric productivity 0.44 g/L/h. The yield of xylitol and volumetric productivity were 0.69 g/g and 0.28 g/L/h respectively from hemicellulosic hydrolysate of sugarcane bagasse after detoxification with activated charcoal and ion exchange resins. The Ca-alginate immobilized D. hansenii cells produced 73.8 g of xylitol from 100 g/L of xylose with a yield of 0.82 g/g and volumetric productivity of 0.46 g/L/h and were reused for five batches with steady bioconversion rates and yields. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Immobilization; Sugarcane bagasse hemicellulose; Thermotolerant Debaryomyces hansenii; xylitol; Xylose